Solid waste generation, composition and potentiality of waste-to-resource recovery in Sylhet City Corporation - Ahmed, Md Jisan; Taher, M A; Reza, Md Al Amin (Journal of Bangladesh Institute of Planners, 2022)
Solid waste generation is increasing with high economic and population growths in Sylhet City Corporation (SCC). Characteristics of solid waste generation are different in many ways in the different cities/urban areas of Bangladesh. SCC is facing severe development challenges in areas like solid waste management and waste-to-resource recovery. SCC and its extended areas are now producing more solid waste than ever before because of accelerated unplanned urbanization, ever-growing tourist pressure and growing urban population. Sooner than later, resources recovery and capacity development in existing solid waste management systems will be required to allow sustainable and resilient growth of SCC. This study was aimed to explore the amount of solid waste generation per day in SCC and its extended areas. It also aimed to examine the current waste composition and the potential for resource recovery from solid waste in SCC. The study found that SCC is now generating a total 375.75 tons of solid waste every day from the households, kitchen markets, medical establishments, hotels, restaurants, and shops. This study has also found that about 90% of solid waste is perishable with high moisture content. The study identified some weaknesses of the existing solid waste management system. Recommendations were made for initiatives to convert waste into resources such as compost fertilizer, solid recovered fuel, and electricity production. This study can directly help the conservancy department of SCC, and possibly of other municipalities in Bangladesh, to formulate their policies and plans. JBIP, Vol. 15, 2022, pp. 43-62